Electrolytic capacitor and method for manufacturing the same

By using a porous anode body and a high-purity dielectric layer in the electrolytic capacitor, the concentration of the second group of metals is limited, and the problems of impurities in the dielectric layer are solved, which significantly reduces the leakage current and improves the performance of the capacitor.

CN115132498BActive Publication Date: 2024-12-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210297938.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2022-03-24
Publication Date
2024-12-27
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

Existing electrolytic capacitors are prone to mix impurities in chemical conversion liquids, resulting in the presence of impurities in the dielectric layer and the tendency to increase leakage current (LC), and the prior art has not effectively solved this problem.

Method used

Using a porous anode body and a high-purity dielectric layer covering its surface, the ratio of the total atomic number of metals in the second group to the first group is below 100 ppm, thereby ensuring the high purity of the dielectric layer and reducing leakage current. The specific method includes using metals such as tantalum, niobium, titanium, aluminum and zirconium as the first group of metals, and metals such as iron, chromium, copper, silicon, molybdenum, sodium and nickel as the second group of metals to control the second in the chemical conversion liquid. The metal concentration in the group was less than 0.03 ppm, and the metal content in the dielectric layer was measured by an analysis method such as ICP.

Benefits of technology

The leakage current of the electrolytic capacitor is significantly reduced, the high purity of the dielectric layer is ensured, the presence of impurities in the dielectric layer is avoided, and the performance of the capacitor is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115132498B_ABST
    Figure CN115132498B_ABST
Patent Text Reader

Abstract

The electrolytic capacitor includes a capacitor element, the capacitor element including a porous anode body, a dielectric layer formed on the surface of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer. The anode body includes a first group of metals, the first group of metals including at least one selected from tantalum, niobium, titanium, aluminum and zirconium. The dielectric layer includes an oxide of the first group of metals and a second group of metals, the second group of metals including at least one selected from iron, chromium, copper, silicon, molybdenum, sodium and nickel. In the dielectric layer, a ratio X of the total number of atoms of the second group of metals to the total number of atoms of the first group of metals is 100 ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. Background Art

[0002] An electrolytic capacitor includes an anode body and a dielectric layer formed on the surface of the anode body. Generally, the dielectric layer is formed by anodizing (chemical conversion treatment) the surface of the anode body. Various anodizing methods have been proposed.

[0003] Patent document 1 discloses a method for manufacturing a solid electrolytic capacitor, in which a valve-acting metal is anodized to form a solid electrolyte on an anode body having an oxide film formed thereon, and then a plurality of the anode bodies are immersed in a rechemical conversion solution provided with a flat electrode, and electricity is passed between the anode bodies and the flat electrode to perform a rechemical conversion treatment, thereby forming a metal layer. Among them, it is proposed to immerse the anode bodies in a rechemical conversion solution in such a manner that the shortest distance T1 between the anode bodies and the shortest distance T2 between the anode bodies and the flat electrode are 0<T2 / T1<5 to perform a rechemical conversion treatment. It is recorded that for the flat electrode, one of stainless steel, carbon, gold, and platinum is used as the material.

[0004] Patent document 2 discloses a manufacturing device for a tantalum electrolytic capacitor using tantalum metal as an anode substrate. It proposes using a mesh or porous tantalum plate as a cathode plate of a chemical conversion device for performing chemical conversion, wherein the chemical conversion is a chemical conversion for forming an anodic oxide film on the anode substrate and a chemical conversion for repairing the anodic oxide film after a solid electrolyte layer such as manganese dioxide is formed on the anodic oxide film by thermal decomposition.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 11-8166

[0008] Patent Document 2: Japanese Utility Model Application Laid-Open No. 55-14728 Summary of the invention

[0009] The quality of the dielectric layer formed by chemically converting the surface of the anode body (anode substrate) affects the magnitude of the leakage current (LC). If impurities are mixed into the dielectric layer, there is a tendency for the LC to increase.

[0010] The chemical conversion treatment of the anode body is performed while the anode body is immersed in a chemical conversion solution in a chemical conversion tank. If the chemical conversion solution contains impurities, the impurities are easily mixed into the dielectric layer.

[0011] However, impurities in the chemical conversion solution have not been fully considered in the past, so impurities may be mixed into the dielectric layer. For example, metals such as stainless steel are generally used in chemical conversion tanks. It has been found that when metals are used in chemical conversion tanks, metal ions are dissolved into the chemical conversion solution and eventually mixed into the dielectric layer.

[0012] An electrolytic capacitor according to one aspect of the present invention comprises a capacitor element, the capacitor element comprising: a porous anode body, a dielectric layer formed on the surface of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer. The anode body comprises a first group of metals, the first group of metals comprising at least one selected from tantalum, niobium, titanium, aluminum, and zirconium. The dielectric layer comprises an oxide of the first group of metals and a second group of metals, the second group of metals comprising at least one selected from iron, chromium, copper, silicon, molybdenum, sodium, and nickel. In the dielectric layer, a ratio X of the total number of atoms of the second group of metals to the total number of atoms of the first group of metals is 100 ppm or less.

[0013] Another aspect of the present invention is a method for manufacturing an electrolytic capacitor, including: a step of preparing an anode body; a step of electrically connecting the anode body to a first electrode for chemical conversion; and a step of oxidizing at least a portion of the surface of the anode body to form a dielectric layer. The step of forming the dielectric layer is performed as follows: a voltage is applied between the first electrode and the second electrode while the anode body electrically connected to the first electrode is immersed in a chemical conversion solution in a chemical conversion tank and the second electrode is immersed in the chemical conversion solution. The anode body includes a first group of metals, and the first group of metals includes at least one selected from tantalum, niobium, titanium, aluminum and zirconium. The mass-based concentration of the second group of metals including at least one selected from iron, chromium, copper, silicon, molybdenum, sodium and nickel contained in the chemical conversion solution is 0.03 ppm or less.

[0014] According to the present invention, the leakage current (LC) of the electrolytic capacitor can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a cross-sectional view schematically showing an example of the electrolytic capacitor of the present invention.

[0016] Figure 2 It is a perspective view schematically showing an example of an anode portion.

[0017] Figure 3 A diagram schematically showing an example of one step of the production method of the present invention.

[0018] Figure 4 It is schematically shown that Figure 3A diagram of an example of a process of a process.

[0019] Description of Reference Numerals

[0020] 100: Electrolytic capacitor

[0021] 110: Capacitor element

[0022] 111: Anode

[0023] 112: Anode lead

[0024] 113: Anode

[0025] 113e1: First end face

[0026] 113e2: Second end face

[0027] 113G: Anode group

[0028] 113s: Side

[0029] 114: Dielectric layer

[0030] 115: Cathode

[0031] 116: Solid electrolyte layer

[0032] 117: Cathode lead layer

[0033] 120: Anode lead terminal

[0034] 121: Anode terminal

[0035] 122: Lead connection part

[0036] 130: Cathode lead terminal

[0037] 131: Cathode terminal

[0038] 132: Connection

[0039] 141: Conductive layer

[0040] 201: Chemical conversion tank

[0041] 202: Chemical conversion fluid

[0042] 210: First electrode

[0043] 220: Second electrode DETAILED DESCRIPTION

[0044] Hereinafter, the embodiments of the electrolytic capacitor and the method for manufacturing the same of the present invention will be described by way of example, but the present invention is not limited to the examples described below. In the following description, there are cases where specific values ​​and materials are illustrated, but other values ​​and materials can be applied as long as the effects of the present invention can be obtained. In this specification, the description of "value A to value B" includes value A and value B, and can be replaced by "value A or more and value B or less".

[0045] (Electrolytic Capacitors)

[0046] The type of the electrolytic capacitor of the present invention is not particularly limited, and may be a solid electrolytic capacitor or a hybrid electrolytic capacitor including liquid and solid electrolytes.

[0047] The electrolytic capacitor has a capacitor element. The capacitor element includes: a porous anode body, a dielectric layer formed on the surface of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer. The anode body may include a porous sintered body as a sintered body of metal powder, or may include a metal foil (anode foil) with a roughened surface. The anode foil and the cathode foil may be wound with a separator to form a capacitor element.

[0048] The anode body includes a first group metal M1, and the first group metal M1 includes a valve action metal. The dielectric layer includes an oxide of the first group metal M1. The dielectric layer can be a chemical conversion film formed by anodizing (chemical conversion treatment) the anode body including the first group metal M1. The first group metal M1 can be at least one selected from tantalum (Ta), niobium (Nb), titanium (Ti), aluminum (Al) and zirconium (Zr).

[0049] The anode body is composed almost entirely of the first group metal M1. However, in addition to the first group metal M1, the anode body may also contain the second group metal M2 as an impurity metal. The content of the second group metal M2 contained in the anode body is, for example, 100 ppm or less, preferably 30 ppm or less, based on mass.

[0050] The dielectric layer is almost entirely composed of oxides of the first group metal M1, that is, composed of the first group metal M1 and oxygen. However, in addition to the first group metal M1, the dielectric layer may also contain the second group metal M2 as an impurity metal. The second group metal M2 may be at least one selected from iron (Fe), chromium (Cr), copper (Cu), silicon (Si), molybdenum (Mo), sodium (Na) and nickel (Ni).

[0051] Here, in the dielectric layer, the ratio X of the total number of atoms of the second group metal to the total number of atoms of the first group metal is 100 ppm or less. The ratio X can be obtained as the ratio of the content rate (OM2) of the second group metal M2 contained in the dielectric layer to the content rate (OM1) of the first group metal M1 contained in the dielectric layer: OM2 / OM1, and has a relationship of ratio X=OM2 / OM1. The second group metal M2 contained in the dielectric layer is a trace amount, and the dielectric layer is composed of a high-purity oxide of the first group metal. By limiting the ratio X to 100 ppm or less, the leakage current (LC) can be significantly suppressed. The ratio X can be 80 ppm or less, 50 ppm or less, or 30 ppm or less.

[0052] When the second group metal M2 exceeds the above range in the dielectric layer, a conductive path is formed in the dielectric layer as an insulator, and leakage current (LC) of the electrolytic capacitor is likely to occur. This phenomenon is believed to occur due to the following reasons: impurity energy levels are generated in the band gap, so that electrons are easily released into the dielectric layer.

[0053] The first group of metals M1 contained in the anode body may be one type or two or more types. The first group of metals M1 contained in the dielectric layer may be one type or two or more types. If the dielectric layer is a chemical conversion film formed by anodizing the anode body, the first group of metals M1 contained in the anode body and the first group of metals M1 contained in the dielectric layer are of the same type.

[0054] The second group of metals M2 that can be included in the anode body can be one type or two or more types. The second group of metals M2 that can be included in the dielectric layer can be one type or two or more types. The second group of metals M2 that can be included in the anode body and the second group of metals M2 that can be included in the dielectric layer can be the same type or different types. For example, there can be a second group of metals M2 that is included only in the dielectric layer. Due to various reasons, the second group of metals M2 may be mixed into the dielectric layer. Generally, compared with the second group of metals M2 that can be included in the anode body, the content of the second group of metals M2 that can be included in the dielectric layer becomes larger.

[0055] When the ratio of the total number of atoms of the second group metal in the anode body to the total number of atoms of the first group metal is defined as ratio Y, ratio X may be greater than 1 and less than 1.2 times relative to ratio Y. Ratio Y may be obtained as the ratio of the content rate (AM2) of the second group metal M2 contained in the anode body to the content rate (AM1) of the first group metal M1 contained in the anode body: AM2 / AM1, and has a relationship of ratio Y=AM2 / AM1. That is, X / Y=(OM2 / OM1) / (AM2 / AM1) may be greater than 1 and less than 1.10, or may be greater than 1 and less than 1.05.

[0056] Here, the ratio X can be measured, for example, by inductively coupled plasma emission spectrometry (ICP). For example, the dielectric layer is dissolved in a heated acid solution (e.g., a mixed acid of hydrofluoric acid, nitric acid, and sulfuric acid), and after filtering out the solution residue, the obtained solution is analyzed by ICP to measure the spectral intensity of the first group of metals M1 and the second group of metals M2. Next, a calibration line is prepared using commercially available standard solutions of the first group of metals M1 and the second group of metals M2, and the content OM1 of the first group of metals M1 and the content OM2 of the second group of metals M2 contained in the dielectric layer are calculated, and the ratio X=OM2 / OM1 is calculated.

[0057] The ratio Y can be measured in the same manner as the ratio X. For example, the anode body is dissolved in a heated acid solution, the solution residue is filtered out, and the obtained solution is analyzed by ICP to measure the spectral intensity of the first group metal M1 and the second group metal M2. Next, a calibration line is prepared using commercially available standard solutions of the first group metal M1 and the second group metal M2, the content AM1 of the first group metal M1 and the content AM2 of the second group metal M2 contained in the anode body are calculated, and the ratio Y=AM2 / AM1 is calculated.

[0058] In addition, the ratio X can be obtained as follows. The anode body having a dielectric layer is completely dissolved in a heated acid solution, and after filtering out the solution residue, the obtained solution A is analyzed by ICP, and the spectral intensity of the first group of metals M1 and the second group of metals M2 is measured. Similarly, the anode body after the dielectric layer is removed is completely dissolved in a heated acid solution, and after filtering out the solution residue, the obtained solution B is analyzed by ICP, and the spectral intensity of the first group of metals M1 and the second group of metals M2 is measured. The concentrations of the first group of metals M1 and the second group of metals M2 in each solution can be obtained using a calibration line, and the ratio X=OM2 / OM1 can be calculated by calculation using the ratio of the dielectric layer in the anode body having a dielectric layer.

[0059] The first group of metals M1 may be, for example, only tantalum (Ta). In this case, the anode body and the dielectric layer do not actually contain valve metals other than tantalum (Ta). Here, "does not actually contain" also includes the case where the anode body and the dielectric layer contain valve metals other than tantalum (Ta) at a content below the detection limit (for example, 1 ppb or less on a mass basis).

[0060] The second group metal M2 may be contained as an impurity in the powder of the first group metal M1 as the raw material of the anode body, or may be dissolved into the chemical conversion solution from a chemical conversion tank having stainless steel as a component and mixed into the dielectric layer.

[0061] The second group metal M2 may be at least one selected from iron (Fe), chromium (Cr) and nickel (Ni). Iron (Fe), chromium (Cr) and nickel (Ni) are elements that are easily contained as impurities in the anode body and the dielectric layer.

[0062] The second group metal M2 may be only iron (Fe). Iron (Fe) is a representative example of the second group metal M2 and is an element most easily contained as an impurity in the anode body and the dielectric layer. Iron (Fe), for example, may be dissolved from a chemical conversion tank having stainless steel as a component into a chemical conversion solution and mixed into the dielectric layer.

[0063] As an example of the structure and components of the electrolytic capacitor of the present invention, an example of a case where the anode body is a sintered body (porous sintered body) of a powder of the first group of metals is described below. The electrolytic capacitor described below includes a capacitor element, an outer body, an anode lead terminal, and a cathode lead terminal. It should be noted that the structure and components of the electrolytic capacitor of the present invention are not limited to the following examples.

[0064] (Capacitor Components)

[0065] The capacitor element includes an anode portion, a dielectric layer and a cathode portion. The anode portion includes an anode body and an anode lead. The dielectric layer is formed on the surface of the anode body. The cathode portion includes a solid electrolyte layer and a cathode lead layer. The solid electrolyte layer is arranged between the dielectric layer formed on the surface of the anode body and the cathode lead layer. These components are not particularly limited, and components used in known electrolytic capacitors can be applied.

[0066] (Anode)

[0067] The anode body can be formed by molding and sintering a powder of a valve metal such as tantalum (Ta), niobium (Nb), titanium (Ti), aluminum (Al), zirconium (Zr), or an alloy thereof using a mold or the like.

[0068] (Dielectric layer)

[0069] The dielectric layer is formed on the surface of the anode body by chemical conversion treatment. The chemical conversion treatment includes the process described in step (iii) of the method for producing an electrolytic capacitor described later.

[0070] (Anode lead)

[0071] The anode lead may be a wire, a strip, a foil, etc. made of metal. The material of the anode lead includes valve-acting metals, copper, etc. A part of the anode lead is embedded in the anode body, and the rest of the anode lead protrudes from the end surface of the anode body.

[0072] (Solid electrolyte layer)

[0073] The solid electrolyte layer is not particularly limited, and a solid electrolyte layer used in a known electrolytic capacitor can be applied. The solid electrolyte layer may be a laminate of two or more different solid electrolyte layers.

[0074] The solid electrolyte layer is configured to cover at least a portion of the dielectric layer. The solid electrolyte layer can be formed using a manganese compound or a conductive polymer. Examples of conductive polymers include polypyrrole, polythiophene, polyaniline, and derivatives thereof. They can be used alone or in combination. In addition, the conductive polymer can be a copolymer of two or more monomers. It should be noted that the derivative of the conductive polymer refers to a polymer with a conductive polymer as the basic skeleton. For example, examples of the derivative of polythiophene include poly(3,4-ethylenedioxythiophene) and the like.

[0075] It is preferred to add a dopant to the conductive polymer. The dopant can be selected according to the conductive polymer, and a known dopant can be used. Examples of the dopant include naphthalenesulfonic acid, p-toluenesulfonic acid, polystyrenesulfonic acid, and salts thereof. In one example, the solid electrolyte layer is formed using poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrenesulfonic acid (PSS).

[0076] The solid electrolyte layer containing the conductive polymer can be formed by polymerizing a raw material monomer on the dielectric layer, or by applying a liquid containing the conductive polymer (and a dopant as needed) to the dielectric layer and then drying it.

[0077] (Cathode extraction layer)

[0078] The cathode lead layer is a conductive layer, and is configured to cover at least a portion of the solid electrolyte layer. The cathode lead layer may include a carbon layer formed on the solid electrolyte layer, and a metal paste layer formed on the carbon layer. The carbon layer may be formed of a conductive carbon material such as graphite and a resin. The metal paste layer may be formed of metal particles (e.g., silver particles) and a resin, and may be formed, for example, by a known silver paste.

[0079] (Cathode lead terminal and anode lead terminal)

[0080] The cathode lead terminal includes a cathode terminal portion exposed from the outer body of the electrolytic capacitor, and a connecting portion connected to the cathode terminal portion. The connecting portion is electrically connected to the cathode portion. For example, the connecting portion can be connected to the cathode lead layer through a conductive layer (such as a silver paste layer). The anode lead terminal includes an anode terminal portion exposed from the outer body of the electrolytic capacitor, and a lead connecting portion connected to the anode terminal portion. The lead connecting portion is connected to the anode lead. Each lead terminal can be formed by processing a metal sheet (including a metal plate and a metal foil) formed of a metal (copper, a copper alloy, etc.) using a known metal processing method.

[0081] (outer body)

[0082] The outer casing is arranged around the capacitor element in such a manner that the capacitor element is not exposed from the surface of the electrolytic capacitor. In addition, the outer casing insulates the anode lead terminal and the cathode lead terminal. Therefore, the outer casing is made of an insulating material. The method for forming the outer casing is not limited and can be formed by a known method. For example, the outer casing can be formed by arranging the material of the outer casing in such a manner as to cover a part of the lead terminal and the capacitor element and curing it. In this way, an electrolytic capacitor can be obtained.

[0083] Figure 1 A cross-sectional view schematically shows an example of the electrolytic capacitor of the present invention. Figure 1 The electrolytic capacitor 100 shown includes a capacitor element 110, an anode lead terminal 120, a cathode lead terminal 130, an outer casing 101, and a conductive layer 141. The capacitor element 110 includes an anode portion 111, a dielectric layer 114, and a cathode portion 115. The anode portion 111 includes an anode body 113 and an anode lead (anode wire) 112. The anode body 113 is a rectangular porous sintered body, and a dielectric layer 114 is formed on the surface. A portion of the anode lead 112 protrudes from one end surface of the anode body 113 toward the front surface 100f of the electrolytic capacitor 100. The other portion of the anode lead is buried in the anode body 113.

[0084] The cathode portion 115 includes a solid electrolyte layer 116 arranged to cover at least a portion of the dielectric layer 114, and a cathode lead layer 117 formed on the solid electrolyte layer 116. The cathode lead layer 117 includes, for example, a carbon layer formed on the solid electrolyte layer 116, and a metal particle layer formed on the carbon layer. The metal particle layer is, for example, a metal paste layer (e.g., a silver paste layer) formed using a metal paste.

[0085] The anode lead terminal 120 includes an anode terminal portion 121 and a lead connection portion 122. The anode terminal portion 121 is exposed at the bottom surface 100b of the electrolytic capacitor 100. The lead connection portion 122 is connected to the anode lead 112. The cathode lead terminal 130 includes a cathode terminal portion 131 and a connection portion 132. The cathode terminal portion 131 is exposed at the bottom surface 100b of the electrolytic capacitor 100. The connection portion 132 is electrically connected to the cathode lead layer 117 through the conductive layer 141.

[0086] The above describes the case where a porous sintered body is used as an anode body, but the present invention can be applied to a wound electrolytic capacitor. A wound electrolytic capacitor includes a plate group, a solid electrolyte and a shell. The plate group includes a wound body, an anode lead and a cathode lead. The wound body is formed by winding an anode body (metal foil), a separator and a cathode foil. The anode lead is connected to the anode body (metal foil), and the cathode lead is connected to the cathode foil. The anode body is formed of a metal including a valve-acting metal. The surface of the anode body is roughened or made porous, and a dielectric layer is formed on the surface. A solid electrolyte is impregnated in the separator. The wound electrolytic capacitor may include a liquid such as an electrolyte. These components are not particularly limited, and known components for wound electrolytic capacitors can be used.

[0087] (Method for manufacturing electrolytic capacitor)

[0088] The manufacturing method of an electrolytic capacitor comprises the following steps (i) to (iii) in sequence. From one point of view, the present invention provides a chemical conversion treatment method for forming a dielectric layer on the surface of an anode body. The chemical conversion treatment method comprises the following steps (i) to (iii), and is performed using a device comprising a chemical conversion tank configured with a chemical conversion treatment solution, a first electrode, a second electrode, and a power supply (e.g., a DC power supply). It should be noted that in the embodiments described below, non-essential components in the method of the present invention may be omitted.

[0089] Here, an example of a production method (or a chemical conversion treatment method) in which the anode body is a sintered body (porous sintered body) of a powder of the first group metal will be described.

[0090] (Process (i))

[0091] Step (i) is a step of preparing an anode body. Step (i) may be a step of preparing a plurality of anode portions including an anode body and an anode lead protruding from a first end surface of the anode body. The anode body and the anode lead are not limited, and known anode bodies and anode leads may be used. Alternatively, the anode portion may be produced by a known method.

[0092] The anode body includes a first group metal M1 as a valve metal. The anode body may be a sintered body of a molded body of a powder of the first group metal M1. The first group metal M1 may be at least one selected from tantalum (Ta), niobium (Nb), titanium (Ti), aluminum (Al) and zirconium (Zr). The first group metal M1 may be, for example, only tantalum (Ta). That is, the anode body may be a sintered body of tantalum (Ta) powder. In this case, valve metals other than tantalum (Ta) are not actually included in the anode body and the dielectric layer.

[0093] exist Figure 21 shows an example of the anode portion 111. The anode portion 111 includes an anode body 113 and an anode lead 112 protruding from a first end surface 113e1 of the anode body 113. The anode body 113 has a second end surface 113e2 on a surface opposite to the first end surface 113e1, and the anode body 113 has a side surface 113s connecting the first end surface 113e1 and the second end surface 113e2. Figure 2 The anode body 113 of the example shown is substantially in the shape of a rectangular parallelepiped and has four side surfaces 113s.

[0094] (Step (ii))

[0095] Step (ii) is a step of electrically connecting the anode body to the first electrode for chemical conversion. Step (ii) may be, for example, a step of connecting a plurality of anode leads connected to a plurality of anode bodies to the first electrode for chemical conversion in a state where a plurality of anode bodies are arranged at intervals along a predetermined direction to form an anode body group. That is, step (ii) is, for example, a state where a plurality of anode parts are arranged at intervals along a predetermined direction, and anode leads of a plurality of anode parts are connected to the first electrode for chemical conversion. The plurality of anode bodies may be arranged in a row or in a matrix.

[0096] The shape of the first electrode is selected according to the configuration of the anode body group. For example, when a plurality of anode bodies are arranged in a row, the first electrode may have a linear shape (e.g., rod-shaped, plate-shaped). When a plurality of anode bodies are arranged in a matrix, the first electrode may be composed of a plurality of linear electrodes, or may be a grid-shaped electrode. The first electrode is electrically connected to the anode lead. Usually the anode lead is fixed to the first electrode by welding or other methods. The material of the first electrode is not particularly limited, and may be a conductive metal (e.g., iron, iron alloy, copper, copper alloy, aluminum, etc.). In order to prevent the second group of metals M2 from being dissolved into the chemical conversion solution, it is desired that the first electrode does not contact the chemical conversion solution.

[0097] The number of anode bodies contained in the anode body group is not limited, and may be in the range of 10 to 200 (e.g., in the range of 40 to 100). The spacing between adjacent anode bodies is also not particularly limited. The spacing may be in the range of 1 to 20 mm (e.g., in the range of 2 to 6 mm). Usually, the spacing is constant, but the spacing may not be constant.

[0098] exist Figure 3 An example of an anode body group is shown in FIG. In an anode body group 113G, a plurality of anode bodies 113 are arranged at intervals along a predetermined direction D, and a plurality of anode leads 112 connected to the plurality of anode bodies 113 are connected to a first electrode 210 for chemical conversion. Figure 3In the embodiment, a plurality of anode bodies 113 are arranged in a row. The first electrode 210 is an elongated plate-shaped electrode extending in a straight line. The anode lead 112 is fixed to the first electrode 210 by welding or the like and is electrically connected thereto.

[0099] (Process (iii))

[0100] Step (iii) includes: in a state where the anode body electrically connected to the first electrode is immersed in a chemical conversion solution in a chemical conversion tank and the second electrode is immersed in the chemical conversion solution, a voltage is applied between the first electrode and the second electrode to oxidize at least a portion of the surface of the anode body to form a dielectric layer. Step (iii) may be, for example, a step where a plurality of anode bodies connected to the first electrode via an anode lead are immersed in the chemical conversion solution, a DC voltage is applied between the first electrode and the second electrode to oxidize at least a portion of the surface of the anode body to form a dielectric layer. In step (iii), the second electrode is, for example, arranged in contact with the chemical conversion solution and along the anode body group.

[0101] In step (iii), the surface of the anode body is oxidized and changed into a dielectric layer. For example, in the case where the anode body is formed of tantalum (Ta), a tantalum oxide layer is formed on the surface of the anode body. The chemical conversion liquid is not particularly limited, and a known chemical conversion liquid used for chemical conversion treatment of the anode body of an electrolytic capacitor can be used. For example, the chemical conversion liquid can use any solution of an acidic aqueous solution, a neutral aqueous solution, or a basic aqueous solution. Examples of acidic aqueous solutions include aqueous phosphoric acid solution, aqueous nitric acid solution, aqueous acetic acid solution, and aqueous sulfuric acid solution. Other examples of chemical conversion liquids include aqueous tartrate solutions, aqueous oxalate solutions, and aqueous tetraborate solutions.

[0102] The mass-based concentration of the second group metal M2 contained in the chemical conversion solution is controlled to be less than 0.03 ppm, and further controlled to be less than 0.01 ppm. As a result of controlling the mass-based concentration of the second group metal M2 contained in the chemical conversion solution to be less than 0.03 ppm, the dielectric layer can be composed of a high-purity oxide of the first group metal. That is, the ratio X=OM2 / OM1 can be limited to less than 100 ppm.

[0103] When calculating the mass-based concentration of the second group of metals M2 contained in the chemical conversion solution, at least one selected from iron (Fe), chromium (Cr), copper (Cu), silicon (Si), molybdenum (Mo), sodium (Na) and nickel (Ni) may be considered as the second group of metals M2. In this case, the mass-based concentration of the total of iron (Fe), chromium (Cr), copper (Cu), silicon (Si), molybdenum (Mo), sodium (Na) and nickel (Ni) contained in the chemical conversion solution is controlled to be less than 0.03 ppm, and further controlled to be less than 0.01 ppm. The second group of metals M2 may be at least one selected from iron (Fe), chromium (Cr) and nickel (Ni). In this case, the mass-based concentration of the total of iron (Fe), chromium (Cr) and nickel (Ni) contained in the chemical conversion solution is controlled to be less than 0.03 ppm, and further controlled to be less than 0.01 ppm. The second group of metals M2 may be only iron (Fe). In this case, the mass-based concentration of iron (Fe) contained in the chemical conversion solution is controlled to be 0.03 ppm or less, and further controlled to be 0.01 ppm or less.

[0104] The second electrode is configured in a manner of contacting the chemical conversion liquid. For example, the second electrode can be immersed in the chemical conversion liquid. In order to prevent the second group of metals M2 from dissolving into the chemical conversion liquid, it is preferred that the material of the second electrode use a metal that is stable during chemical conversion. The material of the second electrode can be, for example, the first group of metals, or it can be at least one selected from tantalum (Ta), niobium (Nb), titanium (Ti), aluminum (Al), zirconium (Zr), platinum (Pt), gold (Au), nickel (Ni), carbon and ITO (indium tin oxide). The second electrode can be in the form of a plate or a mesh.

[0105] From the same point of view, the material constituting the portion in contact with the chemical conversion solution can be selected in such a way that the second group of metals is not dissolved into the chemical conversion solution as much as possible. Such a material can be, for example, the first group of metals, preferably at least one selected from tantalum (Ta), niobium (Nb), titanium (Ti), aluminum (Al), zirconium (Zr), nickel (Ni), carbon and non-metallic materials. The non-metallic material can be resin, glass, etc. At least a portion of the chemical conversion tank can be used as the second electrode.

[0106] The second electrode is configured, for example, in a manner opposite to a second end face of the anode body on the opposite side to the first end face (the end face from which the anode lead protrudes), and at least one of the side faces connecting the first end face and the second end face. For example, the second electrode may be configured in a manner opposite to only the second end face of the anode body, in a manner opposite to only the side face of the anode body, or in a manner opposite to both the second end face and the side face of the anode body. In the case where the second electrode is configured in a manner opposite to the side face of the anode body, the second electrode may be configured in a manner opposite to only the side face of one side of the arranged anode body group. Alternatively, two second electrodes may be configured in a manner of clamping the anode body group. In the case where the electrode (counter electrode) paired with the first electrode is composed of two or more electrodes, at least one of the electrodes is a second electrode having the above-mentioned characteristics.

[0107] exist Figure 4 An example of a device including a chemical conversion cell, a first electrode, and a second electrode is shown in FIG. Figure 4 In the figure, the power supply is omitted. A plurality of anode bodies 113 are connected to the first electrode 210 via the anode lead 112, and are immersed in the chemical conversion solution 202 in the chemical conversion tank 201 as an anode body group 113G. The second electrode 220 is arranged in a manner of being immersed in the chemical conversion solution 202 and facing the second end surface 113e2 of the anode body 113. The second electrode 220 is arranged in a manner of being along the anode body group 113G. In this state, a DC voltage is applied between the first electrode 210 and the second electrode 220. As a result, at least a portion of the surface of the anode body 113 is oxidized to form the dielectric layer 114. At this time, the surface of a portion of the anode lead 112 may also be oxidized.

[0108] By including the steps (i) to (iii), an anode portion having a dielectric layer formed on the surface can be obtained. Therefore, from one viewpoint, the present invention provides a method for manufacturing an anode portion having a dielectric layer formed on the surface. The manufacturing method includes the above steps (i) to (iii).

[0109] By performing steps (i) to (iii) and then performing steps of forming parts necessary for the electrolytic capacitor, an electrolytic capacitor can be obtained. These steps are not limited, and known methods can be applied.

[0110] In a method for manufacturing an electrolytic capacitor in which the anode body is a sintered body of a powder of a first group of metals, a solid electrolyte layer is formed in a manner covering at least a portion of a dielectric layer, and a cathode lead layer is formed on the solid electrolyte layer. A capacitor element is manufactured in this manner. Next, an anode lead terminal is connected to the anode lead, and a cathode lead terminal is connected to the cathode lead layer. Then, an outer casing is formed in a manner covering the capacitor element, a portion of the anode lead terminal, and a portion of the cathode lead terminal. In this manner, an electrolytic capacitor can be obtained.

[0111] In a manufacturing method of an example of an electrolytic capacitor in which the anode body is a wound body of metal foil, in step (i), a wound body formed by winding the anode body (metal foil), a separator and a cathode foil is prepared. The wound body includes an anode portion. The anode portion includes an anode body (metal foil) and an anode lead protruding from the first end face of the anode body (the first end face of the wound anode body). Usually, a dielectric layer is formed on the surface of the anode body (metal foil), but the dielectric layer may not be formed on at least a portion of the end face of the anode body. Therefore, in the portion where the dielectric layer is not formed, a dielectric layer is formed by the above-mentioned steps (ii) and (iii). After the dielectric layer is formed, a capacitor element is manufactured by forming a solid electrolyte layer inside the wound body. By sealing the manufactured capacitor element in a casing, a wound electrolytic capacitor can be obtained. The constituent elements and formation methods of the solid electrolyte layer are not particularly limited, and known constituent elements and formation methods can be used.

[0112] The present invention will be described in more detail with reference to the following examples, but the following examples are not intended to limit the present invention.

[0113] 《Example 1》

[0114] (i) Fabrication of capacitor elements

[0115] (ii) Step of preparing anode body

[0116] Tantalum (Ta) powder is used as the valve metal. The tantalum (Ta) powder is molded into a rectangular parallelepiped by embedding one end of a linear anode lead formed of tantalum (Ta) in the tantalum (Ta) powder, and then the molded body is sintered in a vacuum. Thus, a porous sintered body containing tantalum (Ta) and an anode portion of the anode lead partially embedded in the porous sintered body and the rest protruding from the end surface of the anode body are obtained.

[0117] (i-ii) Step of connecting the anode body to the first electrode

[0118] The produced anode portions 106 were arranged in a row at a certain interval, and the anode lead was welded to the elongated plate-shaped first electrode.

[0119] (i-iii) Step of forming a dielectric layer

[0120] In a state where the anode lead is welded to the anode portion of the first electrode and a portion of the anode lead are immersed in a chemical conversion solution in a chemical conversion tank made entirely of glass, and a second electrode made of tantalum (Ta) is immersed in the chemical conversion solution, a DC voltage is applied between the first electrode and the second electrode, thereby oxidizing the surface of the anode body to form a dielectric layer. A 0.06 mass % aqueous solution of nitric acid is used in the chemical conversion solution. The temperature of the chemical conversion solution is 60°C. The DC voltage is set to 15V and applied for 10 hours. In this way, a uniform chemical conversion film (thickness of about 30nm) of tantalum oxide (Ta2O5) is formed as a dielectric layer on the surface of the anode body and the surface of a portion of the anode lead.

[0121] (i-iv) Formation of solid electrolyte layer

[0122] The anode body having the dielectric layer formed thereon was immersed in the dispersion containing polypyrrole for 5 minutes and then dried at 150° C. for 30 minutes to form a solid electrolyte layer on the dielectric layer.

[0123] (iv) Formation of carbon layer

[0124] A dispersion (carbon paste) in which carbon particles were dispersed in water was applied onto the solid electrolyte layer and then heated at 200° C., thereby forming a carbon layer on the surface of the solid electrolyte layer.

[0125] (i-vi) Formation of Metal Paste Layer

[0126] A silver paste containing silver particles, a binder resin, and a solvent was applied to the surface of the carbon layer, and then heated at 200° C. to form a silver paste layer, thereby obtaining a capacitor element.

[0127] (ii) Fabrication of electrolytic capacitors

[0128] A conductive adhesive material was further applied on the silver paste layer, and the cathode lead terminal was joined to the silver paste layer. The anode lead was joined to the anode lead terminal by resistance welding. Next, each capacitor element joined with the lead terminal was placed in a mold, and sealed with the material of the outer body (thermosetting resin composition) by transfer molding, thereby producing an electrolytic capacitor A1.

[0129] 《Examples 2 to 4》

[0130] Electrolytic capacitors A2 to A4 of Examples 2 to 4 were prepared in the same manner as in Example 1, except that ferric nitrate was dissolved in the chemical conversion solution so as to have an iron (Fe) concentration (ppm by mass) shown in Table 1.

[0131] [evaluate]

[0132] <Leakage Current (LC) Measurement>

[0133] A voltage of 6.3 V was applied to the prepared electrolytic capacitors A1 to A4, and LC was measured after 40 seconds. Table 1 shows relative values ​​of LC, with LC of electrolytic capacitor A4 using a chemical conversion solution having an iron (Fe) concentration of 0.05 ppm as a reference value (100%).

[0134] <Ratio X=Fe / Ta>

[0135] The content rates of tantalum (Ta) and iron (Fe) contained in the dielectric layer were measured by the above method to calculate the ratio X, and the content rates of tantalum (Ta) and iron (Fe) contained in the anode body were measured to calculate the ratio Y. In addition, X / Y was calculated from the calculated ratio X and ratio Y. The results are shown in Table 1.

[0136] [Table 1]

[0137] Capacitors Fe concentration Ratio X[ppm] Ratio Y[ppm] X / Y LC(%) A1 0ppm 80 80 1.00 11 A2 0.01ppm 86 80 1.07 53 A3 0.03ppm 100 80 1.25 92 A4 0.05ppm 110 80 1.38 100

[0138] Industrial Applicability

[0139] The present invention can be applied to an electrolytic capacitor and a method for manufacturing the same.

Claims

1. An electrolytic capacitor comprising a capacitor element, The capacitor element comprises: Porous anode body, a dielectric layer formed on a surface of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer, The anode body comprises a first group of metals, the first group of metals comprising at least one selected from tantalum, niobium, titanium, aluminum and zirconium, The dielectric layer comprises an oxide of the first group of metals and a second group of metals, wherein the second group of metals comprises at least one selected from iron, chromium, copper, silicon, molybdenum, sodium and nickel, In the dielectric layer, a ratio X of the total number of atoms of the second group of metals to the total number of atoms of the first group of metals is 100 ppm or less, The ratio of the total number of atoms of the second group of metals in the anode body to the total number of atoms of the first group of metals is set to ratio Y, and the ratio X is 1 to 1.2 times the ratio Y.

2. The electrolytic capacitor according to claim 1, wherein: The first group of metals is tantalum, The second group of metals is iron.

3. A method for manufacturing the electrolytic capacitor according to claim 1, comprising: The process of preparing an anode body; The step of electrically connecting the anode body to a first electrode for chemical conversion; as well as A step of applying a voltage between the first electrode and the second electrode while the anode body electrically connected to the first electrode is immersed in a chemical conversion solution in a chemical conversion tank and the second electrode is immersed in the chemical conversion solution, thereby oxidizing at least a portion of the surface of the anode body to form a dielectric layer, The anode body comprises a first group of metals, the first group of metals comprising at least one selected from tantalum, niobium, titanium, aluminum and zirconium, The concentration of the second group of metals including at least one selected from iron, chromium, copper, silicon, molybdenum, sodium and nickel contained in the chemical conversion solution is 0.03 ppm or less on a mass basis.

4. The method for manufacturing an electrolytic capacitor according to claim 3, wherein: The material of the second electrode is at least one selected from tantalum, niobium, titanium, aluminum, zirconium, platinum, gold, nickel, carbon and indium tin oxide (ITO).

5. The method for manufacturing an electrolytic capacitor according to claim 3 or 4, wherein: The material constituting the portion of the chemical conversion tank in contact with the chemical conversion solution is at least one selected from tantalum, niobium, titanium, aluminum, zirconium, nickel, carbon, and non-metallic materials.

6. The method for manufacturing an electrolytic capacitor according to claim 3 or 4, wherein: The first group of metals is tantalum, The second group of metals is iron.